Letter Name (Alphabet) and Letter Sound (A Field Study at KinderStation Preschool (TK Cahaya Bangsa Utama) Yogyakarta) - Yohana Ika Harnita Sari (Master Program in Linguistics, Diponegoro University, 2016)
Teaching reading to early learners is begun with teaching how to identify and pronounce each letter in a word. Therefore, every preschool or primary school has its own technique in teaching pronunciation as the stepping stone to teach reading to its students. KinderStation Preschool (TK Cahaya Bangsa Utama) Yogyakarta is one of the preschools in Yogyakarta that teaches reading to the students using phonics approach, especially analytic phonics. This paper has two objectives. First, it is to describe the application of phonics at KinderStation Preschool. Second, it aims to describe the result of the application of phonics at KinderStation Preschool. To answer those goals, field study is utilized by doing observation and interview. The employment of analytic phonics covers three points; they are the learning materials, the learning media, and the learning process applied in KinderStation Preschool. The application of phonics in teaching reading results on the development of students’ reading fluency. The students have automatic recognition of letters and are able to pronounce words easily and correctly.